2016
DOI: 10.1111/nph.13955
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the roles of nonstructural carbohydrates in forest trees – from what we can measure to what we want to know

Abstract: Summary Carbohydrates provide the building blocks for plant structures as well as versatile resources for metabolic processes. The nonstructural carbohydrates (NSC), mainly sugars and starch, fulfil distinct functional roles, including transport, energy metabolism and osmoregulation, and provide substrates for the synthesis of defence compounds or exchange with symbionts involved in nutrient acquisition or defence. At the whole‐plant level, NSC storage buffers the asynchrony of supply and demand on diel, seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
456
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 599 publications
(515 citation statements)
references
References 188 publications
14
456
0
3
Order By: Relevance
“…During droughts the nitrogen reserves are filled with foliage nitrogen which is recycled prior to leaf fall, while the nitrogen reserves are depleted when water availability and subsequent growth is high. Defoliation experiments indicate that plants can rely on substantial amounts of internally stored reserves of carbohydrate and nutrients which allow them to survive multiple defoliation events (Hartmann and Trumbore, 2016); however, the extent to which plants rely on internal storages is strongly species dependent (Piper and Fajardo, 2014), and the role of nutrients is often overlooked (Hartmann and Trumbore, 2016). Nonetheless, Ichie and Nakagawa (2013) showed that in Dryobalanops aromatica stored phosphorus accounted for 67.7 % of the total phosphorus requirements for reproduction, while stored N accounted for only 19.7 %, indicating substantial nutrient reserves in tropical trees.…”
Section: Control Simulationmentioning
confidence: 99%
“…During droughts the nitrogen reserves are filled with foliage nitrogen which is recycled prior to leaf fall, while the nitrogen reserves are depleted when water availability and subsequent growth is high. Defoliation experiments indicate that plants can rely on substantial amounts of internally stored reserves of carbohydrate and nutrients which allow them to survive multiple defoliation events (Hartmann and Trumbore, 2016); however, the extent to which plants rely on internal storages is strongly species dependent (Piper and Fajardo, 2014), and the role of nutrients is often overlooked (Hartmann and Trumbore, 2016). Nonetheless, Ichie and Nakagawa (2013) showed that in Dryobalanops aromatica stored phosphorus accounted for 67.7 % of the total phosphorus requirements for reproduction, while stored N accounted for only 19.7 %, indicating substantial nutrient reserves in tropical trees.…”
Section: Control Simulationmentioning
confidence: 99%
“…In recent debates on the possible limitation of carbohydrate reserves, it was stated that limitation rarely occurs [16], possibly only for trees exposed to long lasting drought periods [17]. The transport of photosynthetically derived carbon from leaves to belowground biomass is often reduced under drought hindering optimal development of a functional root system, which can lead to a lack of essential nutrients and to higher mortality rates in the long-term [17,18]. A better understanding of the metabolic processes in declining trees is of great interest for predicting forest response to future warming.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the dynamics of storage is also essential to correctly represent the C balance in models (Hartmann and Trumbore, 2016). If, for example, a direct growth limitation is implemented into models, how should the surplus of accumulated photosynthates be treated?…”
Section: Introductionmentioning
confidence: 99%